2018
DOI: 10.1016/j.aim.2018.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-constant characters: Motivation, classification and applications

Abstract: In [13], initially motivated by questions about the Hodge line bundle of a Hodge-type Shimura variety, we singled out a generalization of the notion of minuscule character which we termed quasi-constant. Here we prove that the character of the Hodge line bundle is always quasi-constant. Furthermore, we classify the quasi-constant characters of an arbitrary connected, reductive group over an arbitrary field. As an application, we observe that, if µ is a quasi-constant cocharacter of an Fp-group G, then our cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…In the classical theory this amounts to the case that the VHS V is polarized of weight one. Here we recover the results of our joint work with Koskivirta [12]. The second example provides explicit formulas for grif(G, µ, r) when r = Ad is the adjoint representation, essentially in terms of the Coxeter number of the underlying root system.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the classical theory this amounts to the case that the VHS V is polarized of weight one. Here we recover the results of our joint work with Koskivirta [12]. The second example provides explicit formulas for grif(G, µ, r) when r = Ad is the adjoint representation, essentially in terms of the Coxeter number of the underlying root system.…”
Section: Introductionsupporting
confidence: 65%
“…The condition "orbitally p-close" is a weakening of certain p-smallness conditions, while "quasi-constant" generalizes "minuscule". See [12] for more on quasi-constant (co)characters.…”
Section: 44mentioning
confidence: 99%
“…[38], Th.1.4.4). The Hodge character η ω of a symplectic embedding ϕ ′ : (G, X) ֒→ (GSp(2g), X g ) is quasi-constant (Def.…”
mentioning
confidence: 96%
“…In [4], the authors classified quasi-constant (co)characters and showed that the notion 'quasi-constant' naturally unifies those of minuscule and co-minuscule. In particular, if k is algebraically closed and G is simple, then a character χ ∈ X * (T) is quasi-constant if and only if it is a multiple of a fundamental weight (relative some choice of simple roots ∆ ⊂ Φ) which is either minuscule or co-minuscule [4, Th.…”
mentioning
confidence: 99%
“…In [4], see esp. §5.2, we argued why it seemed that'quasi-constant' was perhaps a more natural notion than either 'minuscule' or 'co-minuscule' separately.…”
mentioning
confidence: 99%